2020
DOI: 10.9734/arjass/2020/v12i230187
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency Analysis of Pineapple Production at Madhupur Upazila of Tangail District, Bangladesh

Abstract: The main objective of this study is to analyse the technical efficiency and its determinants of pineapple production at Madhupur upazila of Tangail district in Bangladesh. Cross-section data from a sample of 100 pineapple producers during the 2016-17 cropping season were collected by applying multistage random sampling technique. Farm specific technical efficiency scores were estimated using the Cobb-Douglas stochastic frontier production function approach. Empirical findings show that the estimated technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The finding showed that the farm size coefficient (0.007) was positive which implies that there is an opportunity to expand pineapple production with an increase in the area dedicated to pineapple cultivation. Similar results were reported by Amarasuriya et al, (2010); Das et al, (2014); Thingbaijam et al, (2015); Balogun et al, (2018); Akter et al, (2020) were they found that area under pineapple cultivation had significant effect on the production.…”
Section: Production Frontier Estimatessupporting
confidence: 87%
“…The finding showed that the farm size coefficient (0.007) was positive which implies that there is an opportunity to expand pineapple production with an increase in the area dedicated to pineapple cultivation. Similar results were reported by Amarasuriya et al, (2010); Das et al, (2014); Thingbaijam et al, (2015); Balogun et al, (2018); Akter et al, (2020) were they found that area under pineapple cultivation had significant effect on the production.…”
Section: Production Frontier Estimatessupporting
confidence: 87%